2006
DOI: 10.1007/s10608-006-9004-2
|View full text |Cite
|
Sign up to set email alerts
|

Rumination and Excessive Reassurance-Seeking in Depression: A Cognitive–Interpersonal Integration

Abstract: The purpose of this study was to conduct a preliminary investigation into the crosssectional associations between depression, rumination, and excessive reassuranceseeking. Guided by conceptual linkages between these variables, ruminative response style was examined as both a potential moderator and as a potential mediator of the association between depressive symptoms and excessive reassuranceseeking in a sample of undergraduate students (N = 244). Results from this investigation suggest that rumination mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 21 publications
1
28
0
1
Order By: Relevance
“…Previous studies, the majority of which were conducted in the United States, consistently showed that ruminative response style is related to psychopathology, including bulimic symptoms (e.g., Nolen-Hoeksema, Stice, Wade, & Bohon, 2007), drinking (e.g., Caselli et al, 2010), NSSI (Hilt, Cha, & Nolen-Hoeksema, 2008), and excessive reassurance-seeking (e.g., Weinstock & Whisman, 2007). On the contrary, rumination variable (as assessed by the CERQ) did not correlate with all of the dysregulated behaviors (such as NSSI and bulimia) in the current study, and had the weakest link with the emotional cascades construct.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies, the majority of which were conducted in the United States, consistently showed that ruminative response style is related to psychopathology, including bulimic symptoms (e.g., Nolen-Hoeksema, Stice, Wade, & Bohon, 2007), drinking (e.g., Caselli et al, 2010), NSSI (Hilt, Cha, & Nolen-Hoeksema, 2008), and excessive reassurance-seeking (e.g., Weinstock & Whisman, 2007). On the contrary, rumination variable (as assessed by the CERQ) did not correlate with all of the dysregulated behaviors (such as NSSI and bulimia) in the current study, and had the weakest link with the emotional cascades construct.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, people involved in romantic relationships marked by depression may have questions about whether they are a worthy mate (e.g., Coyne, 1976;Shaver, Schachner, & Mikulincer, 2005), how much their partner supports and loves them (e.g., Coyne, 1976), the sincerity of their partner's reassurances (e.g., Joiner, Metalsky, Katz, & Beach, 1999;Starr & Davila, 2008), the way their partner views their relationship (e.g., Katz & Beach, 1997), and who is to blame for negative outcomes within their relationship (e.g., Joiner, 2000;Joiner & Timmons, 2009). They also may doubt their ability to make sense of social situations (e.g., Jacobson, 2007) and may spend time ruminating about the effects of depression (e.g., Weinstock & Whisman, 2007).…”
Section: Depression and Relational Uncertaintymentioning
confidence: 99%
“…For example, depressed patients who are high in rumination report more difficulties in intimate relationships (Lam et al 2003) and baseline ruminative brooding predicts diminished relationship satisfaction 3 months later in individuals with a history of major depression (Pearson et al 2010). Another study found an association between rumination and excessive reassurance-seeking (Weinstock and Whismann 2007). Finally, Müller et al (2013) found depressive rumination during pregnancy to be predictive of reduced postpartum mother-infant bonding.…”
Section: Introductionmentioning
confidence: 99%